2005
DOI: 10.1038/sj.ijo.0802870
|View full text |Cite
|
Sign up to set email alerts
|

The effects of physical activity and body mass index on cardiovascular, cancer and all-cause mortality among 47 212 middle-aged Finnish men and women

Abstract: OBJECTIVE:To examine the association of physical activity and body mass index (BMI), and their combined effect, with the risk of total, cardiovascular disease (CVD) and cancer mortality. DESIGN: Prospective follow-up study. SUBJECTS: In all, 22 528 men and 24 684 women aged 25-64 y at baseline having 7394 deaths during a mean follow-up of 17.7 y. MEASUREMENT: A self-administered questionnaire data on smoking, socioeconomic factors, physical activity and medical history, together with measured height, weight, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
211
3
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(223 citation statements)
references
References 44 publications
6
211
3
3
Order By: Relevance
“…Previous studies have hypothesized that high physical activity may attenuate the increased risk of mortality that is related to adiposity [16,31]. In our population sample, the beneficial effects of physical activity on mortality seem to be present in non-obese men and women (BMI<30) only.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Previous studies have hypothesized that high physical activity may attenuate the increased risk of mortality that is related to adiposity [16,31]. In our population sample, the beneficial effects of physical activity on mortality seem to be present in non-obese men and women (BMI<30) only.…”
Section: Discussionmentioning
confidence: 62%
“…Some population studies and reviews detected a reduced risk of cancer mortality through enhanced physical activity among men [25], women [11] or both sexes [16,17,26,27], but none of them has independently examined work, transportation, household and leisure time physical activity. A large prospective follow-up study from Finland [16] reported a 21% and 27% lower risk of cancer mortality for men and women, respectively, when comparing high versus low occupational and leisure time physical activity. With regard to our study sample, moderately active individuals almost halved their risk of premature deaths due to cancer, while vigorously active persons reduced their risk by almost two thirds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since questions on alcohol consumption were different between the first two surveys (1972 and 1977) and the latter surveys, the participants were categorised as either abstainers or alcohol users. Physical activity included occupational, commuting and leisure-time physical activity, and results were merged and regrouped into three categories: low, moderate and high [27][28][29][30][31][32][33][34]. At the study site, specially trained research nurses measured blood pressure, height and weight using a standardised protocol [26].…”
Section: Measurementsmentioning
confidence: 99%
“…It has been proposed that physical activity could counteract the risk of obesity. Physical activity has been shown to weaken, but not eliminate the heightened risk associated with excess weight [15,34,35]. However, many studies to date measure only one component of total activity, such as leisure time or occupational physical activity, which may not be a true representation of actual total physical activity.…”
Section: Introductionmentioning
confidence: 99%